Fish bone-catalyzed methanolysis of waste cooking oil - Sulaiman, Sarina; Amin, M.H.M. (Univ Diponegoro, Kampus Undip Tembalang, Semarang, Indonesia, 2016)
The use of cheaper alternative such as waste cooking oil as substitute to vegetable oil can reduce the overall production cost of biodiesel. This research focuses on the investigation of the kinetic of waste cooking oil methanolysis using heterogeneous waste catalyst. Fish bone waste was used as the catalyst for the methanolysis of waste cooking oil. The kinetic data obtained from this study can be used to optimize the process of biodiesel production. The effects of temperature and catalyst amount were varied between 50- 65 °C and 4-10 wt % respectively. The kinetic of transesterification of waste oil, the reaction rate constant (k) and activation energy (EA) at 55, 65 and 65 °C were determined. The highest yield of biodiesel, 86 % were achieved at 6 wt% of catalyst amount, mixing of 300 rpm, methanol to oil ratio of 18:1 and reaction temperature of 65 °C. The activation energy (Ea) was 34.12 kJ/mol. This study also proves that transesterification process is not affected by the internal mass transfer due to the Thiele modulus value between 0-1.69.